Dynamic Representation of Taste-Related Decisions in the Gustatory Insular Cortex of Mice - Vincis, Roberto (Curr Biol, 2020)
Research over the past decade has established the gustatory insular cortex (GC) as a model for studying howprimary sensory cortices integrate sensory,affective, and cognitive signals. This integration occurs through time-varyingpatterns of neural activity. Selective silencing of GC activity during specific temporal windows provided evidence forGC’s role in mediating taste palatability and expectation. Recent results also suggest that this areamay play a role in decision making. However, existing data are limited to GC involvement in controlling the timing of stereotyped, orofacial reactions to aversive tastants during consumption. Here,we present electrophysiological, chemogenetic, and optogenetic results demonstrating the key role of GCin the executionof a taste-guided, reward-directed decision-making task. Mice were trained in a two-alternative choice task, in which they had to associate tastants sampled from a central spout with different actions (i.e., licking either a left or a right spout). Stimulus sampling and action were separated by a delay period. Electrophysiological recordings revealed chemosensory processing during the sampling period and the emergence of task-related, cognitive signals during the delay period. Chemogenetic silencing of GCimpaired task performance. Optogenetic silencing of GC allowed us to tease apart the contribution of activity during sampling and delay periods. Although silencing during the sampling period had no effect, silencing during the delay period significantly impacted behavioral performance, demonstrating the importance of the cognitive signals processed by GC in driving decision making. Altogether, our data highlight a novel role ofGCin controlling taste-guided, reward-directed choices and actions.